A conceptual model of customer satisfaction: Moderating effects of price sensitivity and quality seekers in the airline industry - Abdul Razak Abdul Hadi; Mohd Hanafia Huridi; Syeliya Md Zaini; Zalina Zainudin (Contemporary Economics, 2019)
Passenger satisfaction and loyalty are crucial for success in the airline industry. To achieve customer satisfaction and loyalty, it is important that airlines provide high-quality services. This paper examines different elements of service quality in the airline industry, including the moderating effects of price sensitivity and quality seekers on the level of passenger satisfaction. The moderating effect of price sensitivity on passenger satisfaction has received less consideration in the existing literature. Service quality has been divided into three main categories: preflight, in-flight, and postflight services. This paper provides a conceptual framework for assessing the moderating effects of price sensitivity and service quality on passenger satisfaction. The study was conducted by performing a literature review of existing studies of the topic and related issues. Information was obtained from journal articles. The literature was reviewed for accuracy, relevancy, and other validating elements. The findings reveal that the service quality of all three categories has a positive effect on passenger satisfaction. The results indicate that passenger satisfaction consequentially translates to passenger loyalty (Elkington, 2004). The findings indicate that price sensitivity and quality seekers have a significant impact on the relationship between service quality and the level of passenger satisfaction. High price sensitivity reduces the positive effects of service quality on passenger satisfaction. Low price sensitivity increases the positive effects of service quality on passenger satisfaction. Existing literature agrees that customer satisfaction is subjective and varies across consumers. Therefore, analyzing the correlation between service quality and satisfaction has been a complex task (Briliana, 2018).
Keywords: M31; M10; L10; 330; Service quality; Customer satisfaction; Customer loyalty; Price sensitivity; Quality seekers; Airline